Determination of urinary isoursodeoxycholic acid and ursocholic acid in patients during ursodeoxycholic acid treatment - NAKAMURA, Kimihide; YOKOHAMA, Shiro; TAKAMOTO, Shujiro; Aso, Kazunobu; YONEDA, Masashi; MAKINO, Isao; AOSHIMA, Masaru; NAKADE, Yukiomi; SATO, Yoichi (Kanzo, 1998)
Urinary isoursodeoxycholic acid (isoUDCA) and ursocholic acid (UCA) which are metabolites of ursodeoxycholic acid (UDCA) were analyzed by gas-liquid chromatography in 8 patients with gall stone (GS), 20 with chronic hepatitis (CH) and 13 with compensated liver cirrhosis (LC) during oral administration of UDCA 600mg/day. The concentration of total bile acid in fasted urine was 22.48±3.8, 60.94±11.7 and 104.32±28.7 (Mean±SE, μmole/l) in GS, CH and LC, respectively. In patients with GS, the percentage of UDCA in total bile acid was significantly lower, however, the percentages of isoUDCA and UCA were significantly higher than CH and LC patients (UDCA, isoUDCA, UCA: 46.3±6.8, 20.9±5.8, 7.2±3.5 in GS, 64.3±2.6, 10.3±1.7, 4.0±0.9 in CH, 73.3±2.7, 5.1±1.0, 1.9±0.5 (Mean±SE, %) in LC, respectively). Furthermore, the percentage of UDCA in total 7β-hydroxy bile acid significantly increased following liver disease (64.8±9.1, 81.6±2.3 and 92.2±1.3 (Mean±SE, %) in GS, CH and LC, respectively) and was the negative correla ion with serum albumin. Present study suggests that the measurement of UDCA and its metabolites in urine of patient during UDCA administration may be an useful test to evaluate the impairment of hepatic function and enterohepatic circulation.